Back Cover: Integrating 31P DOSY NMR Spectroscopy and Molecular Mechanics as a Powerful Tool for Unraveling the Chemical Structures of Polyoxomolybdate‐Based Amphiphilic Nanohybrids in Aqueous Solution (Chem. Eur. J. 18/2014). Issue 18 (25th April 2014) - Shestakova , Pavletta; Absillis, Gregory; Martin‐Martinez, Francisco J.; De Proft, Frank; Willem, Rudolph; Parac‐Vogt, Tatjana N.
<x xml:space="preserve">Abstract</x> It looks like magic but in the end it′s all straightforward! Linear polyoxometalate‐based hybrids have been synthesized by simply mixing (NH4)6Mo7O24 and 1, 8‐octanediphosphonic acid in aqueous solution. By using a multi‐technique approach, combining 31P DOSY, 95Mo NMR spectroscopy and molecular mechanics calculations, the nature and length of these hybrids were determined. For more details, see the Full Paper by T. N. Parac‐Vogt et al. on p. 5258 ff.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>